Generation I and Generation II Elastomeric Chains Characteristics Comparison in Artificial Saliva Immersion - Subroto, Marisa Icha Aisya; Putri, Anindita Permata Hardarini; Putri, Leliana Sandra Devi Ade; Hidayati, Lusi (Brazilian Dental Science, 2020)
Objective: To determine the force decay and discoloration in Generation I and Generation II elastomeric chain on artificial saliva immersion. Material and methods: Generation I and Generation II elastomeric chains stretched on an acrylic board and immersed in artificial saliva for 1, 7, 14, 21, and 28 days according to the group of days. On each specified day, the force of each sample measured by an orthodontic force gauge and the magnitude of the force obtained is entered to the formula to find out the force decay in percentage, whereas discoloration of each sample analyzed by the color reader with CIE Lab analysis. Results: The force decay between Generation I and Generation II elastomeric chains showed a statistically significant difference in every group of days, in which Generation II is more effective in maintaining stretch force. Similar to force decay, the discoloration in Generation I elastomeric chains on the 14th day showed significant value and Generation II elastomeric chains were more stable in maintaining color compared to Generation I. Conclusions: over the entire research period time, Generation II elastomeric chains are more stable in maintaining stretch forces and color compared to Generation I elastomeric chains. KEYWORDS Discoloration; Elastomeric chain; Force decay; Generation I; Generation II.